Comparative evaluation of rescuegrass (Bromus catharticus) lines for forage yield and quality under mediterranean climate conditions - DONMEZ, HASAN BEYTULLAH (The Indian Journal of Agricultural Sciences, 2026)
Developing high-yielding and quality forage crops adapted to Mediterranean conditions is essential to meet the increasing feed demand in the region. This research was conducted for two consecutive years in 2020–21 and 2021–22 under Mediterranean climatic conditions in Adana, Turkiye to determine the yield and quality of seven rescuegrass Bromus catharticus Vahl. breeding lines developed by selection breeding. The experiment was conducted in a randomized complete block design (RCBD) with three replications. Significant effects of year, line, and year × line interactions were observed for most traits. Plant height increased from 76.1 cm (establishment year) to 111.4 cm (second year), while tiller number rose from 8.0 to 19.3/plant. Line 17 exhibited the highest fresh forage yield (19.9 t/ha) and dry matter yield (6.8 t/ha) in the second year, significantly outperforming other lines. Forage quality analysis revealed that Lines 13 and 14 showed superior nutritional value, with crude protein contents of 13.68% and 13.92%, respectively, and lower fiber fractions. Acid detergent fiber ranged from 41.99% (Line 13) to 45.08% (Line 17), while relative feed value varied between 62.3 and 69.3. Strong negative correlations were observed between yield and quality parameters, indicating a typical yield-quality trade-off in forage breeding. These results demonstrated substantial genetic variation among rescuegrass lines and identify Line 17 for high-yield breeding objectives and Line 13 for quality-focused programmes adapted to Mediterranean conditions. Future studies should focus on multi-location trials and molecular characterisation to develop improved rescuegrass cultivars for Mediterranean conditions.